Anestesia epidural em cutias (Dasyprocta azarae) submetidas à ovariossalpingohisterectomia - Martins, Leandro Luis; de Oliveira, Fabricio Singaretti; Toniollo, Gilson Hélio [UNESP]; Rodrigues, Valeska; Pauloni, Ana Paula; Machado, Marcia Rita Fernandes (Universidade Federal de Santa Catarina (UFSC), 2010)
In this research, the epidural anesthesia technique in nulliparous and non non-nulliparous submitted to ovarysalpingohysterectomy was studied. These are rodents belonging to the Missina Palmeira Zancaner municipal zoo of catanduva in São Paulo. The tranquilization was achieved using azaperone (4mg/kg) and meperidine (4mg/kg) followed by injection of cetamine (20mg/kg) and xylazine (0.4mg/kg), intramuscularly from the same syringe. Subsequently, lidocaine (5mg/kg) was injected into the lumbosacral space. The time of latency of the anesthesic association (4.0[plus or minus]1.51min), time of latency of epidural lidocaine (6.87[plus or minus]2.35min) and time of analgesia (115.0[plus or minus]12.49min) were analyzed, in addition to rectal temperature, which decreased 2.12[plus or minus]0.86[degree]C on average from the beginning of the anesthesia to the end of its effective time. All animals recovered satisfactorily without presenting signs of excitation or complications due to the epidural tecnique. It was concluded that the balanced anesthesia tecnique provided adequate analgesia during a time considered sufficient for several procedures, by means of low doses of xylazine and ketamine.
Epidural anesthesia in agoutis (Dasyprocta azarae)